Analysis of Student Satisfaction with Digital-Based Learning Media Assisted by Baamboozle - Nurhasanah, Sifa; Muhammad, Taofik; Taufiq, Muhammad (Design Journal, 2025)
This study evaluates student satisfaction with Baamboozle educational game-based learning media among fifth-grade students. The research employed quantitative descriptive methods using a 5-point Likert scale questionnaire administered to 18 students at SDN 1 Cihaurbeuti. Data analysis through Jamovi software revealed varying satisfaction levels across three measured aspects. Students rated user experience and application performance as "Satisfied" (3.73 and 4.12 respectively), while interface appearance received "Moderately Satisfied" ratings (3.21). The overall satisfaction score reached 3.66, falling within the "Satisfied" category. Students particularly appreciated the application's responsiveness (4.39) and stability (4.17), but expressed challenges with navigation and menu visibility (2.94). The findings suggest that while Baamboozle effectively engages elementary students, its interface design could benefit from simplification to better accommodate young users. These results offer practical guidance for educators selecting digital learning tools and developers creating age-appropriate educational media for elementary school settings.